Proactive versus Reactive Therapeutic Drug Monitoring: Why, When, and How? - Manar Shmais; Miguel Regueiro; Jana G. Hashash (Inflammatory Intestinal Diseases, 2021)
Background: Up to a third of inflammatory bowel disease) patients show primary nonresponse to antitumor necrosis factor (anti-TNF) biological therapy, and of those who respond, up to 40% develop secondary loss of response (LOR). Therapeutic drug monitoring (TDM) plays a crucial role in assessing patients with LOR to guide therapy by giving more of the drug or switching to a different biological agent. Although reactive TDM is suggested or recommended by the majority of gastroenterology associations, proactive TDM seems to be more controversial. Summary: In this article, we discuss the updated guidelines on TDM and will also discuss the available data supporting proactive and reactive TDM in patients with Crohn’s disease and those with ulcerative colitis using the different available biological agents. Key Messages: Therapeutic drug monitoring (TDM) is a valuable tool to aid in inflammatory bowel disease (IBD) therapy optimization. Reactive TDM is widely accepted in IBD patients with suspected loss of response, especially in those receiving antitumor necrosis factor (anti-TNF) agents. Proactive TDM is emerging as a reasonable approach to patients initiated on anti-TNF therapy, specifically infliximab and, to some extent, adalimumab, particularly for patients with severe ulcerative colitis and fistulizing Crohn’s disease. Similarly, TDM may play a role in patients considering de-escalation from combination therapy. To date, proactive TDM is not widely applied to ustekinumab and vedolizumab and more data are required before this becomes part of clinical practice.